Food safety policy and management in UK and KSA hospitals - Alrasheed, Ali (2019)
Outbreaks of foodborne illness continue to present major challenges for hospitals. This is a particular issue for Saudi Arabia whereby food handlers can be employed despite not having relevant certification or training in food safety processes. The purpose of this study is to critically analyse food safety and hygiene in seven state hospitals in Riyadh, Kingdom of Saudi Arabia so as to establish the knowledge, behaviour and attitudes of Ministry of Health Hospital supervisors, contracted catering supervisors and contracted catering workers engaged in these hospitals. In order to come to these conclusions, this research has first made a comparison of the food safety policies of five NHS Trust hospitals in the UK to identify examples of best practice. It has then surveyed 242 people working as either catering workers, catering supervisors, or MOH supervisors in seven hospitals in Riyadh in order to understand their knowledge of food safety management systems, such as HACCP. Comparing and contrasting knowledge on food safety processes enables a better understanding of how and why foodborne illnesses emerge and is believed to be the first comparative study of all type of hospital staff in Saudi Arabia. Finally, a policy for food safety management has been created based on this research, and in consultation with a community of practice, with the hope that it will be implemented in Saudi hospitals.